Reactive and Pre-planned Agility in Young Tennis Players - Ales Germic (Baltic Journal of Sport and Health Sciences)
Background: In tennis, movement efficiency can be described as agility, which is crucial for adapting to the fast-paced and unpredictable nature of the game and affects a player’s ability to position themselves effectively and react to their opponent’s shots. While most studies focus on pre-planned movements, fewer address the cognitive and reactive components that mirror real match scenarios, highlighting the need for a more comprehensive approach to assessing agility in tennis.